Radiolaria occurrences of IODP Hole 386-M0084D - Michael Strasser; Ken Ikehara; Jeremy D Everest; Lena Maeda; Katharina Hochmuth; Hannah Grant; Margaret S Stewart; Noriaki Sakurai; Takahiro Yokoyama; Rui Bao; Piero Bellanova; Morgane Brunet; et al. (PANGAEA, 2025)
Results of radiolarian analyses from the above given hole of International Ocean Discovery Program (IODP) Expedition 386 (Japan Trench Paleoseismology). The offshore phase of this expedition took place between 2021-04-13 and 2021-06-01 onboard Japanese R/V Kaimei from and to Yokosuka, Japan, followed by an onshore phase onboard D/V Chikyu between 2022-02-14 – 2022-03-15. During the offshore phase, samples for radiolarian analyses were taken from the end of split cores at 2 m intervals. These were complemented during the onshore phase with samples from event layers identified from X-ray CT images. Samples in this dataset where categorized depending on their sedimentary regime by the following type key: E = event, H = hemipelagic, ? = unknown. Slides prepared from these samples were partially examined at 50 exttimes to 400 exttimes using a Zeiss Axio Imager.A1m POL-1 optical microscope on board Chikyu. For further details on sample preparation see methods chapter in0.167emStrasser, M. et al., 2023 https://doi.org/10.14379/iodp.proc.386.102.2023